Yield-phenology relations and water use efficiency of maize (Zea mays L.) in ridge-furrow mulching system in semiarid east African Plateau - Fei Mo (Nature Portfolio, 2017)
Abstract Yield-phenology relation is a critical issue affecting rainfed maize field productivity in semiarid east African Plateau (EAP). We first introduced Chinese ridge-furrow mulching (RFM) system to EAP, using three maize cultivars with early-, mid- and late-maturing traits as test materials. A two-year field experiment was conducted in a semiarid farm of Kenya from 2012 to 2013. Three treatments were designed: alternative ridge and furrow with transparent plastic mulching (FT), with black plastic mulching (FB) and without mulching (CK). We found that FT and FB significantly increased soil moisture and accelerated crop maturity across two growing seasons. Leaf area and shoot biomass were increased by 30.2% and 67.5% in FT, 35.2% and 73.5% in FB, respectively, compared with CK. Grain yield, water use efficiency and economic output were increased by 55.6%, 57.5% and 26.7% in FT, and 50.8%, 53.3% and 19.8% in FB, respectively. Optimal yield and economic benefit were observed in late-maturing cultivar due to increased topsoil temperature in FT in 2012 (cool), and in early-maturing cultivar owing to cooling effect in FB in 2013 (warm). Our study suggested RFM system, combined with crop phenology selection, be a promising strategy to boost maize productivity and profitability in semiarid EAP.